Related Fators With Giving Exclusive ASI In The Area Work Of Astambul Health Center In 2019 - Febria, Zahara (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2022)
Exclusive breastfeeding can reduce morbidity and mortality in children. Based on data from the South Kalimantan Provincial Health Office in 2017 the coverage of exclusive breastfeeding in Astambul Health Center in 2016 was (38.1%) and 2017 experienced a decline, namely (22.60%). Factors that cause failure in exclusive breastfeeding are influenced by many things, namely factors of mother's knowledge, mother's attitude, family support (husband), support of health personnel, trust, and so on. This study aims to determine the Factors Associated with Giving Exclusive Breastfeeding in the Work Area of ​​Astambul Health Center in 2019. This research uses Analytical Survey method with Cross Sectional approach. The population in the study of mothers who have babies> 6-12 months in the Astambul Health Center Working Area. A sample of 167 people. The sampling technique is accidental sampling. Data analysis using Chi Square statistical test (ɑ = 0.05). The results showed that 167 mothers as many as 93 people (55.7%) gave exclusive breastfeeding. Good knowledgeable mothers as many as 131 people (78.4), mothers behave positively as many as 92 people (55.1%), mothers get family support (Husband) as many as 97 people (58.1%), mothers get support from health workers as many as 118 people (70.7%), mothers have negatif beliefs as many as 95 people (43.1%). The results of statistical tests show there is a relationship of knowledge (ρ = 0.005), maternal attitudes (ρ = 0.004), family support (husband (ρ = 0.003), support for health workers (ρ = 0.008), maternal trust (ρ = 0.003) with breastfeeding exclusive.The conclusion of the study is that there is a relationship between knowledge, attitude, family support (husband), support of health workers, and trust in exclusive breastfeeding